Plastic recycling awareness among student in campus - Mohd Nasir, Siti Nur Najwa (2017)
Plastic is a synthetic material that people use it on daily basic. The user of plastics is increasing day by day, therefore, recycling is important to reduce the waste of plastics that has been used.Student lives surrounded by plastics materials like in the classroom, office, cafe and student accommodation.The level of awareness among UUM students towards plastic recycling is still unknown and no empirical evidence.The aim of this study is to identify the perception of Universiti Utara Malaysia (UUM) students towards plastic recycling and to determine the level of awareness about the recycling of plastics that has been used through awareness activities and further contribute to the sustainable development of society, which requires some planning to implement best practices.This study has selected UUM students as respondents.The study employs quantitative approach in which the questionnaires are distributed among students.The focus of this study is about the environment, by recycling the plastic is linked to the environment.The benefit that regarding this topic is student can personally play an important role in reducing plastic pollution and increasing recycling rates for a healthier environment in student life.